2021
DOI: 10.1007/s10652-021-09791-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of increasing riverbank vegetation density on flow dynamics across an asymmetrical channel

Abstract: Over the last two decades, the role of vegetation in the environmental and ecological restoration of surface water bodies has received much attention. In this context, the momentum exchange between the flow through the main channel and the riparian zone is a key mechanism. The primary goal of this study is to investigate the role of bank vegetation density on flow dynamics across the whole channel. This experimental study presents the major findings from a series of flow measurements across a channel having a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…This indicates that the flow conditions in and around the vegetation patch were primarily a function of vegetation characteristics rather than reach‐scale conditions or bed morphology (e.g., Diehl, Wilcox, et al., 2017; Etminan et al., 2018; Ji et al., 2023; Västilä & Järvelä, 2018), at least at the scale of the morphologic changes observed in this study. In both experiments, streamwise velocity within the vegetation patch was reduced to 60%–75% of that in the freestream owing to increased vegetative roughness, while flow constriction in the adjacent main channel increased the velocity by approximately 5%–20% (Figure 2b), which agreed with previous research on sparse uniform vegetation in open channels (e.g., Caroppi et al., 2022; Kim et al., 2015; Lightbody et al., 2019; Valyrakis et al., 2021). Interestingly, the side channel had reduced flow velocities compared with the freestream, which contrasts with previous observations of flow acceleration (〉〈uu0 $\left\langle \frac{u}{{u}_{0}}\right\rangle $ > 1) in the gap between narrowly spaced dense patches (e.g., Meire et al., 2014; Vandenbruwaene et al., 2011).…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that the flow conditions in and around the vegetation patch were primarily a function of vegetation characteristics rather than reach‐scale conditions or bed morphology (e.g., Diehl, Wilcox, et al., 2017; Etminan et al., 2018; Ji et al., 2023; Västilä & Järvelä, 2018), at least at the scale of the morphologic changes observed in this study. In both experiments, streamwise velocity within the vegetation patch was reduced to 60%–75% of that in the freestream owing to increased vegetative roughness, while flow constriction in the adjacent main channel increased the velocity by approximately 5%–20% (Figure 2b), which agreed with previous research on sparse uniform vegetation in open channels (e.g., Caroppi et al., 2022; Kim et al., 2015; Lightbody et al., 2019; Valyrakis et al., 2021). Interestingly, the side channel had reduced flow velocities compared with the freestream, which contrasts with previous observations of flow acceleration (〉〈uu0 $\left\langle \frac{u}{{u}_{0}}\right\rangle $ > 1) in the gap between narrowly spaced dense patches (e.g., Meire et al., 2014; Vandenbruwaene et al., 2011).…”
Section: Discussionsupporting
confidence: 91%
“…This direction of change is consistent with Trail Canyon reaches with denser bank vegetation (Figure 10). Increased bank vegetation has also been shown to increase bed shear stress through feedbacks with depth and velocity (Valyrakis et al., 2021). Interestingly, Figure 9 indicates that the width scaling of sparsely vegetated Woodruff and Trail reaches is similar in spite of grain size differences.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed mechanism is increased hydraulic roughness from vegetation leading to higher adjacent turbulence and shear stresses, including near river banks (e.g., Hopkinson & Wynn, 2009; Yager & Schmeeckle, 2013). However, bank vegetation can slow near‐bank velocities and reduce local shear stresses as well (e.g., Valyrakis et al., 2021). Bed vegetation may also enhance bed deposition in places, potentially shallowing and widening channels (e.g., Molina et al., 2009; Tooth & Nanson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The vegetation can instead destabilize the riverbank by scouring the toe region and leading to mass failure. Their study idealized the bank as non‐erodible and the vegetation as rigid cylinders (Li, Liu, & Huai, 2022; Liu, Valyrakis, & Williams, 2017; Meftah, de Serio, & Mossa, 2014; Valyrakis, Liu, Turker, & Yagci, 2021; Yang, Bai, & Xu, 2018). Studies have suggested that tension cracks occur in a non‐cohesive soil riverbank (Arai et al, 2018; Liang, Jaksa, Ostendorf, & Kuo, 2015).…”
Section: Introductionmentioning
confidence: 99%